A disaggregated analysis of monetary policy effects on the agricultural sector in Nigeria - Ogbuabor, Jonathan E.; Anthony-Orji, Onyinye I.; Manasseh, Charles O.; Orji, Anthony (Applied Studies in Agribusiness and Commerce, 2020)
This study provides a disaggregated analysis of the effects of monetary policy shocks on the agricultural sector in Nigeria from 1981Q1 to 2016Q4. The study utilized the generalized impulse responses and the normalized generalized forecast error variance decompositions from an underlying VAR model, which are order-invariant. The four monetary policy variables used in the study are interbank call rate, monetary policy rate, broad money supply and exchange rate; while the four agricultural sub-sectors investigated are crop production, forestry, fishing and livestock. The study also controlled for the general price level and other economic activities in the overall economy. The findings indicate that the aggregate agricultural sector and its various sub-sectors consistently responded negatively to unanticipated monetary tightening in most of the forecast horizon; while the immediate impact of monetary policy shocks is transmitted to the agricultural sector through the interest rate and money demand (credit) channels. The findings further indicate that apart from these two channels, the roles of monetary policy rate and exchange rate are non-negligible in the long-run. The role of money supply channel in spreading monetary policy shocks to the agricultural sector remained muted all through. The study concludes that the monetary authority should evolve interest rate, credit, and exchange rate policies that will promote the development of the agricultural sector in Nigeria.JEL CODES: E52; N50; C22; N57